Administered activity and outcomes of glass versus resin 90Y microsphere radioembolization in patients with colorectal liver metastases - Srinivas, Shyam M.; Nasr, Elie C.; Kunam, Vamsi K.; Bullen, Jennifer A.; Purysko, Andrei S. (Journal of Gastrointestinal Oncology; Vol 7, No 4 (August 01, 2016): Journal of Gastrointestinal Oncology, 2016)
Background: Given the differences in size, specific activity, and dosing methods for glass yttrium-90 microspheres (90Y-glass) and resin 90Y microspheres (90Y-resin), these therapies may expose the liver to different amounts of radiation, thereby affecting their efficacy and tolerability. We aimed to compare the prescribed activity of 90Y-glass and 90Y-resin for real-world patients undergoing selective internal radiation therapy (SIRT) for liver-dominant metastatic colorectal cancer (mCRC) and to assess efficacy and safety outcomes in these patients. Methods: We examined the records of 28 consecutive patients with unresectable colorectal liver metastases treated with SIRT between June 2008 and May 2011 at our institution. Using baseline CT and MR images, we calculated a projected activity as if we had used the other product and compared it to the actual prescribed activity of 90Y-glass and 90Y-resin for each SIRT treatment per manufacturer guidelines. Progression and adverse events were evaluated at follow up visits. Survival was analyzed by the Kaplan-Meier method. Results: For 90Y-glass treatments with a mean prescribed 90Y activity of 1.77 GBq, the mean projected 90Y-resin activity was 0.84 GBq. For 90Y-resin treatments with a mean prescribed 90Y activity of 1.05 GBq, the mean projected 90Y-glass activity was 2.48 GBq. The median survival was 9.3 months versus 18.2 months for 90Y-glass and 90Y-resin, respectively (P=0.292). During the second year after SIRT, the hazard ratio of death for patients treated with 90Y-glass versus 90Y-resin was 4.0 (95% CI: 1.3, 12.3; P=0.017). No significant difference in progression, adverse events or liver toxicity was observed. Conclusions: Using manufacturer recommended guidelines, 90Y-resin delivers significantly less activity than 90Y-glass to patients with liver-dominant mCRC undergoing SIRT with no significant difference in adverse events and a trend toward improved survival.